Dynamic contribution of recycled components from the subducted Pacific slab: Oxygen isotopic composition of the basalts from 106 Ma to 60 Ma in North China Craton. Issue 2 (18th February 2017) - Liu, Jia; Wang, Zi‐Zhen; Yu, Hao‐Ran; Xia, Qun‐Ke; Deloule, Etienne; Feng, Min
Abstract: How the materials derived from the stagnant Pacific slab contributed to the mantle sources of the mafic rocks in east China is still in hot debate. In this work, δ 18 O (Vienna standard mean ocean water) values of clinopyroxene phenocrysts in the oceanic island basalts (OIB)‐type mafic rocks from 106 Ma to 60 Ma in the east North China Craton (NCC) were measured by secondary ion mass spectrometry. Our data show that for all of the samples, the δ 18 Ocpx are dominantly higher than that of the clinopyroxene from normal mid‐oceanic ridge basalt (5.4–5.8‰), which confirms the role of recycled oceanic crust (ROC) in their mantle sources. Combining the δ 18 O data of basalts and the lithospheric mantle in the literature, we found that in the southeast NCC, upper and lower ROC components alternately appeared in the mantle sources of basalts, but these ROC components are consistently different from that in the lithospheric mantle, while in the northern NCC, the recycled components in the sources seem to be persistently from upper ROC. These observations suggest that (1) these mafic OIB‐type rocks are most likely derived from the convective asthenosphere and (2) the contribution of components from the Pacific oceanic slab into the NCC upper mantle was dynamic, without a simple temporal trend. This new knowledge calls for the reconsideration of the existing models of the thinning process of the NCC lithospheric mantle, and it warns against simply using the chemical composition of basalts to infer the evolution of lithosphere. Key Points: The δ 18 O of the 106–60 Ma basalts in NCC were measured by SIMS The δ 18 O of the basalts are different from that of the lithospheric mantle OIB‐type rocks in NCC were most likely derived from the convective asthenosphere, rather than the lithospheric mantle